Advancing our understanding of the associations between social media use and well-being - Valkenburg, Patti M.; Beyens, Ine; Meier, Adrian; Vanden Abeele, Mariek (Current Opinion in Psychology, 2022)

A license to procrastinate? Self-licensing and self-compassion as predictors of self-forgiveness for online procrastination - Meier, Adrian; Meltzer, Christine E.; Reinecke, Leonhard (25th Annual Conference of the Media Uses and Effects division of the DGPuK, 2019)

Alles eine Frage der digitalen Autonomie? Die Rolle von Autonomie in der digitalen Kommunikation für psychologische Grundbedürfnisse und psychische Gesundheit im Alltag - Meier, Adrian (Medien- und Kommunikationswissenschaft, 2018)
Digital autonomy, defined here as self-determined behaviour in private interpersonal digital communication, may have become a key factor for mental health in our permanently connected everyday lives. Drawing on self-determination theory, this study investigates how individual differences concerning the satisfaction or frustration of autonomy needs in digital interpersonal communication affect general need satisfaction and frustration as well as mental health in everyday life. Results of a diary study of N=532 student smartphone users show that those whose need for autonomy in digital communication is more satisfied experienced slightly higher general need satisfaction (i.e. relatedness, competence, and autonomy) and eudemonic well-being (i.e. authenticity). In contrast, users who reported to have suffered more frustration regarding their need for autonomy in digital communication also showed slightly more frustration of general relatedness, competence and autonomy needs, as well as increased perceived stress in their daily lives. Autonomy, thus, appears to be a fruitful concept, differentiating between positive and negative effects of digital communication. <br

A longitudinal investigation of adolescents’ exposure to the positivity bias, envy, inspiration and the moderating role of social media literacy - Schreurs, Lara; Meier, Adrian; Vandenbosch, Laura (Etmaal van de Communicatiewetenschap, 2022)

“Always on” and always distracted? The mediating role of Internet use for the effects of trait procrastination on psychological well-being. - Reinecke, Leonard; Meier, Adrian; Aufenanger, Stefan; Beutel, Manfred E.; Dreier, Michael; Quiring, Oliver; Stark, Birgit; Woelfling, Klaus; Müller, Kai W. (9th Biennial Procrastination Research Conference, 2015)

At least three episodes or at least two hours? Proposal for a definition and measurement of binge watching as TV series viewing behavior - Granow, Viola; Meier, Adrian; Reinecke, Leonard (24th Annual Conference of the Media Uses and Effects division of the DGPuK, 2018)

#authentic? Differences in users’ state authenticity across Instagram stories and posts - Kreling, Rebekka; Meier, Adrian; Reinecke, Leonhard (71st Annual Conference of the ICA, 2021)

Being permanently connected is a "state of mind": Development and validation of the online vigilance scale - Reinecke, Leonard; Meier, Adrian; Hefner, Dorothée; Reich, Sabine; Rieger, Diana; Klimmt, Christoph; Vorderer, Peter (62nd Annual Conference of the DGPuK,, 2017)

Beyond Active-Passive: Towards the Next Stage of Social Media and Mental Health Research - Meier, Adrian; Ellison, Nicole; Reinecke, Leonard; Valkenburg, Patti M. (2026)
How social media impact users’ mental health and well-being is a critical question discussed fiercely by publics around the globe and researchers across disciplines. To overcome challenges of earlier “screen time” research, many recent studies adopted the active-passive approach. This model dichotomizes social media use into “active” social exchanges and “passive” consumption, with active use yielding social benefits and passive use resulting in harmful upward comparison and envy. Yet, this model has produced surprisingly inconsistent evidence, sparking recent theoretical debates and extensions. Here, we critically synthesize six remaining challenges for the active-passive approach and develop an agenda that outlines why and how the field needs to go beyond active-passive. Specifically, we envision three routes for future research alongside an integrated communication-centered model, which proposes to focus research efforts on message effects, cross-platform experiences, and technology features and affordance
https://cris.fau.de/converis/publicweb/Publication/335324418
Keywords: social media; active-passive use; mental health; well-being; media-affects

Beyond screen time: Exploring effects of different smartphone use log metrics on situational well-being - Klingelhoefer, Julius; Gilbert, Alicia; Adrian, Christoph; Meier, Adrian (30th Annual Conference of the Media Uses and Effects division of the DGPuK, 2024)

Computer-mediated communication and mental health: A computational scoping review of an interdisciplinary field - Meier, Adrian; Domahidi, Emese; Günther, Elisabeth (The Oxford Handbook of Digital Technology and Society, 2020)
The relationship between computer-mediated communication (e.g., Internet or social media use) and mental health has been a long-standing issue of debate. Various disciplines (e.g., communication, psychology, sociology, medicine) investigate computer-mediated communication in relation to a great variety of negative (i.e., psychopathology) and positive (i.e., well-being) markers of mental health. We aim at charting this vast, highly fragmented, and fast growing literature by means of a scoping review. Using methods of computational content analysis in conjunction with qualitative analyses, we map 20 years of research based on 1,780 study abstracts retrieved through a systematic database search. Results reveal the most common topics investigated in the field, as well as its disciplinary boundaries. Our review further highlights emerging trends in the literature and points to unique implications for how future research should address the various relationships between computer-mediated communication and mental health.<br
Keywords: computational content analysis; computer-mediated communication; Internet; social media; mental health; scoping review

Computer-mediated communication, psychological well-being, and psychopathological symptoms: A computational scoping review of an interdisciplinary field - Meier, Adrian; Domahidi, Emese; Günther, Elisabeth; Reinecke, Leonhard (68th Annual Conference of the ICA, 2018)

Computer-mediated communication, social media, and mental health: A conceptual and empirical meta-review - Meier, Adrian; Reinecke, Leonard (Communication Research, 2021)
Computer-mediated communication (CMC), and specifically social media, may affect the mental health (MH) and well-being of its users, for better or worse. Research on this topic has accumulated rapidly, accompanied by controversial public debate and numerous systematic reviews and meta-analyses. Yet, a higher-level integration of the multiple disparate conceptual and operational approaches to CMC and MH and individual review findings is desperately needed. To this end, we first develop two organizing frameworks that systematize conceptual and operational approaches to CMC and MH. Based on these frameworks, we integrate the literature through a meta-review of 34 reviews and a content analysis of 594 publications. Meta-analytic evidence, overall, suggests a small negative association between social media use and MH. However, effects are complex and depend on the CMC and MH indicators investigated. Based on our conceptual review and the evidence synthesis, we devise an agenda for future research in this interdisciplinary field.
CRIS-Team Scopus Importer:2021-02-02
Keywords: computer-mediated communication; mental health; meta-analysis; social media; well-being

Conceptualizing and assessing digital flourishing - Janicke-Bowles, Sophie; Buckley, Tess; Rey, Rikishi; Wozniak, Tayah; Meier, Adrian; Lomanowska, Anna (71st Annual Conference of the ICA, 2021)

Corrigendum to ““Facebocrastination”? Predictors of using Facebook for procrastination and its effects on students' well-being” (Computers in Human Behavior (2016) 64 (65–76) (S0747563216304411) (10.1016/j.chb.2016.06.011)) - Meier, Adrian; Reinecke, Leonard; Meltzer, Christine E. (Computers in Human Behavior, 2017)
The authors regret a copy and paste error in the method section of Study 1 (p. 69). One of the four items of our measure of procrastination with Facebook is not reported correctly. Instead of the correct item (“I used Facebook while procrastinating upcoming work.”) the item “I used Facebook although I had more important things to do.” is listed twice in the respective paragraph (last paragraph in the left text column on p. 69). The authors would like to apologize for any inconvenience caused.
CRIS-Team Scopus Importer:2021-02-02

Daily Digital Balance: Disconnection From Digital Media Can Improve Situational Well-Being - Gilbert, Alicia; Klingelhoefer, Julius; Meier, Adrian (75th Annual Conference of the International Communication Association, 2025)

Debate club: “Passive social media use harms mental health and well-being!" - Meier, Adrian; Krause, Hannes-Vincent (12th Biannual Conference of the Media Psychology division of the DGPs, 2021)

Digital aufatmen: Positive Auswirkungen von Digital Disconnection auf das psychologische Wohlbefinden im Alltag - Gilbert, Alicia; Klingelhoefer, Julius; Meier, Adrian (31st Annual Conference of the Media Uses and Effects division of the DGPuK, 2025)

Digital autonomy is key? The role of autonomous online communication for need satisfaction and psychological well-being in daily life - Meier, Adrian (63rd Annual Conference of the DGPuK, 2018)

Digital flourishing: Conceptualizing and assessing positive perceptions of mediated social interactions - Janicke-Bowles, Sophie H.; Buckley, Tess M.; Rey, Rikishi; Wozniak, Tayah; Meier, Adrian; Lomanowska, Anna (Journal of Happiness Studies, 2023)
Recent research started to apply concepts of well-being to the context of computer mediated communication (e.g., social media, instant messaging). While much research investigates negative perceptions of mediated social interactions (e.g., “problematic” or “addictive” social media use), a multi-dimensional measure that taps into users? positive perceptions is sorely lacking. The present research therefore develops the first comprehensive measure of digital flourishing, defined as positive perceptions of mediated social interactions. Building on a qualitative pre-study that aided the construction of the Digital Flourishing Scale (DFS), Study 1 (N = 474) employed exploratory factor analysis to reveal five subdimensions of digital flourishing. The preregistered Study 2 (N = 438) confirmed these five dimensions, yielding five reliable items per subscale and initial construct validity with three psychological needs from self-determination theory (SDT; competence, autonomy, relatedness) which were used as an underlying well-being framework for the development of the DFS. The preregistered Study 3 generated further construct validity by directly relating DFS to well-being. The scale is relevant for researchers and practitioners alike to better understand how users perceive their mediated interactions to impact mental health and well-being.
CRIS-Team Scopus Importer:2023-02-17
Keywords: social media; flourishing; well-being; scale development; self-determination theory

Disconnecting from what? Digital detox effects beyond the device and application level - Klingelhoefer, Julius; Meier, Adrian (Digital Disconnection Studies Beyond Borders preconference of the 72nd Annual Conference of the ICA, 2022)

Does passive social media use harm well-being? An adversarial review - Meier, Adrian; Krause, Hannes-Vincent (Journal of Media Psychology, 2022)
Research into the effects of social media on well-being often distinguishes "active" and "passive" use, with passive use supposedly more harmful to well-being (i.e., the passive use hypothesis). Recently, several studies and reviews have begun to question this hypothesis and its conceptual basis, the active/passive dichotomy. As this dichotomy has become a staple of social media research but evidence challenging its validity is mounting, a comprehensive debate on its pros, cons, and potential future is needed. This adversarial review brings together two voices - one more supportive, and the other more critical - toward the active/passive model. In constructive dialogue, we summarize and contrast our two opposing positions: The first position argues that the active/passive dichotomy is a useful framework because it adequately describes how and why passive use is (more) harmful for well-being. The second position challenges the validity of the dichotomy and the passive use hypothesis specifically. Arguments are presented alongside (a) the empirical basis, (b) conceptualization, and (c) operationalization of active and passive use, with particular focus on the passive use hypothesis. Rather than offering a conciliatory summary of the status quo, the goal of this review is to carve out key points of friction in the literature on the effects of social media through fruitful debate. We summarize our main agreements and unresolved disagreements on the merits and shortcomings of the active/passive dichotomy. In doing so, this review paves the way for researchers to decide whether and how they want to continue applying this lens in their future work.
CRIS-Team WoS Importer:2022-11-04

Escaping to games? Escapism and procrastination as predictors of problematic computer game use among adolescents - Meier, Adrian; Lentz, Tobias (61st Annual Conference of the DGPuK, 2016)

Exposure to the positivity bias and adolescents’ differential longitudinal links with social comparison, inspiration and envy depending on social media literacy - Schreurs, Lara; Meier, Adrian; Vandenbosch, Laura (Current Psychology, 2022)
Social media literacy is assumed to protect adolescents from negative social media effects, yet research supporting this is lacking. The current three-wave panel study with a four-month interval among N = 1,032 adolescents tests this moderating role of social media literacy. Specifically, we examine between- vs. within-person relations of exposure to the positivity bias on social media, social comparison, envy, and inspiration. We find significant positive relations between these variables at the between-person level. At the within-person level, a different pattern of results occurred: higher exposure to others’ perfect lives on social media was related to increased inspiration, and higher social comparison was related to increased envy, yet both associations only occurred in one of the two time intervals. Additionally, no within-person associations between exposure to positive content and envy were significant, nor between exposure and social comparison or social comparison and inspiration. These results thus seem more complex than traditional paradigms of selective and transactional media effects assume. Furthermore, multiple group tests showed that the within-person cross-lagged relation between social comparison and envy only occurred for adolescents with low affective social media literacy. The moderating role of social media literacy was not supported in any other instances. The results overall point at the need to instruct affective social media literacy to help adolescents navigate positively biased social media platforms in a healthy way.<br

"Facebocrastination"? Predictors of using Facebook for procrastination and its effects on students’ well-being - Meier, Adrian; Meltzer, Christine E.; Reinecke, Leonard (66th Annual Conference of the ICA, 2016)

Facebocrastination? Predictors of using Facebook for procrastination and its effects on students' well-being - Meier, Adrian; Reinecke, Leonard; Meltzer, Christine E. (Computers in Human Behavior, 2016)
Procrastinating with popular online media such as Facebook has been suggested to impair users' wellbeing, particularly among students. Building on recent procrastination, self-control, and communication literature, we conducted two studies (total N = 699) that examined the predictors of procrastination with Facebook as well as its effects on students' academic and overall well-being. Results from both studies consistently indicate that low trait self-control, habitual Facebook checking, and high enjoyment of Facebook use predict almost 40 percent of the variance of using Facebook for procrastination. Moreover, results from Study 2 underline that using Facebook for the irrational delay of important tasks increases students' academic stress levels and contributes to the negative well-being effects of Facebook use beyond the academic domain. The implications of investigating procrastination as a specific pattern of uncontrolled and dysfunctional media use are discussed with regard to research on the uses and effects of ubiquitous online media. (C) 2016 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2021-02-02
Keywords: Facebook; procrastination; self-control; social network sites; university students; well-being

Feeling authentic on social media: Subjective authenticity across Instagram Stories and Posts - Kreling, Rebekka; Meier, Adrian; Reinecke, Leonard (Social Media + Society, 2022)
Self-presentation on social network sites (SNS) such as Instagram is often assumed to be inauthentic or even fake. While authenticity on SNS has been linked to increased well-being, most research has investigated it either monolithically (e.g., via screen time measures) or with regard to stable self-presentations (e.g., in Facebook profiles). In contrast, this study compares subjective authenticity perceptions within users and between self-presentations via two SNS features—Stories vs. Posts. Drawing on the affordances approach, we theorize and test whether and how Stories produce greater state authenticity than Posts. Results from a preregistered within-subjects study comparing self-reports on N = 489 Posts and N = 546 Stories from N = 202 Instagram users show that by allowing more spontaneous self-presentation, Stories indeed produced (slightly) higher authenticity perceptions than Posts. However, subjective authenticity was high in both features, indicating that they similarly offer a space for authentic online self-presentation.
Keywords: authenticity; affordances; self-presentation; masspersonal communication; social media

Gefangen zwischen Selbstkontrollversagen und Normverstoß? Die Effekte des Messaging-Verhaltens von Nutzer*innen bei der Bearbeitung von Aufgaben auf negative selbstbezogene Emotionen - Halfmann, Annabell; Meier, Adrian; Reinecke, Leonard (29th Annual Conference of the Media Uses and Effects division of the DGPuK, 2023)

Getting things done while staying connected? The effects of messenger usage on feelings of guilt - Halfmann, Annabell; Meier, Adrian (65th Annual Conference of the DGPuK, 2020)

Guilt and media use - Reinecke, Leonard; Meier, Adrian (The International Encyclopedia of Media Psychology, 2020)
Media use is often referred to as a “guilty pleasure.” In fact, a growing number of studies provide empirical evidence of a high prevalence of guilt reactions to media use. Negative self‐conscious emotions such as guilt are elicited by actions or events that are incongruent with the individual's personal standards or identity goals. In the context of media use, guilt reactions can be triggered by perceived incongruence with personal standards on three different levels of evaluation: (i) Media users may perceive that specific media content (e.g., pornography or graphic violence) conflicts with personal or external standards. (ii) Guilt can also be the result of user actions performed within interactive media (e.g., immoral behavior in a computer game or on social media). (iii) Finally, guilt may also be triggered by negative appraisal of media use as an activity per se. This is particularly likely if media use is perceived as meaningless or if it conflicts with other situational goals and obligations. Extant research has linked guilt reactions to decreased media enjoyment and media‐induced recovery as well as impaired situational well‐being.<br
Keywords: appraisal; media enjoyment; moral disengagement; self‐conscious emotions; self‐control; well‐being

Habitual social media and smartphone use are linked to task delay for some, but not all, adolescents - Meier, Adrian; Beyens, Ine; Siebers, Teun; Pouwels, J. Loes; Valkenburg, Patti M. (Journal of Computer-Mediated Communication, 2023)
There is a popular concern that adolescents' social media use, especially via smartphones, leads to the delay of intended, potentially more important tasks. Automatic social media use and frequent phone checking may especially contribute to task delay. Prior research has investigated this hypothesis through between-person associations. We advance the literature by additionally examining within-person and person-specific associations of automatic social media use and mobile phone checking frequency with each other and task delay. Preregistered hypotheses were tested with multilevel modeling on data from 3 weeks of experience sampling among N = 312 adolescents (ages 13-15), including T = 22,809 assessments. More automatic social media use and more frequent phone checking were, on average, associated with more task delay at the within-person level. However, heterogeneity analyses found these positive associations to be significant for only a minority of adolescents. We discuss implications for the media habit concept and adolescents' self-regulation.
CRIS-Team WoS Importer:2023-06-02

How and when do mobile media demands impact well-being? Explicating the integrative model of mobile media use and need experiences (IM³UNE) - Schneider, Frank; Lutz, Sarah; Halfmann, Annabell; Meier, Adrian; Reinecke, Leonard (12th Biannual Conference of the Media Psychology division of the DGPs, 2021)

How and when do mobile media demands impact well-being? Explicating the integrative model of mobile media use and need experiences (IM3UNE) - Schneider, Frank M.; Lutz, Sarah; Halfmann, Annabell; Meier, Adrian; Reinecke, Leonard (71st Annual Conference of the ICA, 2021)

How and when do mobile media demands impact well-being? Explicating the Integrative Model of Mobile Media Use and Need Experiences (IM³UNE) - Schneider, Frank M.; Lutz, Sarah; Halfmann, Annabell; Meier, Adrian; Reinecke, Leonard (Mobile Media and Communication, 2022)
Using mobile media can be both detrimental and beneficial for well-being. Thus, explaining how and when they elicit such effects is of crucial importance. To explicate boundary conditions and processes for digital well-being, this article introduces the Integrative Model of Mobile Media Use and Need Experiences IM³UNE. Instead of assuming mobile media to be pathogenic, the IM³UNE offers a salutogenic perspective-it focuses on how we can stay healthy when using mobile media ubiquitously in daily life. More specifically, the model assumes that both the satisfaction and the frustration of basic psychological needs are key underlying mechanisms linking demanding mobile media use to well-being. However, the impact of these mechanisms is contingent on how users perceive, appraise, act on, and make sense of mobile media demands according to their global orientation to life (i.e., their sense of coherence, SOC). Integrating prior work, we theoretically link mindfulness, self-control, and meaningfulness to SOC's central facets, arguing that they represent crucial personal resources required to cope with mobile media demands. Thus, the offers an integrative framework, guiding further research towards a more nuanced study of mobile media's effect on well-being.
CRIS-Team WoS Importer:2021-12-03

How guilt and self-forgiveness mediate the effects of online procrastination on well-being - Reinecke, Leonard; Meier, Adrian; Meltzer, Christine E. (9th Biennial Procrastination Research Conference, 2015)

How to become a pro in procrastination: Predictors of using Facebook for procrastination - Meier, Adrian; Meltzer, Christine E.; Reinecke, Leonard (20th Annual Conference of the Media Uses and Effects division of the DGPuK, 2014)

Inspired by friends: Adolescents' network homophily moderates the relationship between social comparison, envy, and inspiration on Instagram - Noon, Edward John; Meier, Adrian (Cyberpsychology Behavior and Social Networking, 2019)
Research on the negative psycho-emotional implications of social comparisons on social network sites such as Instagram has rapidly accumulated in recent years. However, little research has considered the extent to which such comparisons can elicit positive motivational outcomes for adolescent users, specifically inspiration. Furthermore, little is known about whether it matters whom young people compare themselves to on Instagram (i.e., network composition) and how this may modulate the emotional outcomes of Instagram social comparisons. The present study thus sought to determine how adolescents' Instagram comparisons of ability associate with inspiration through the mechanism of benign and malicious envy. We further examined whether two key aspects of network composition - perceived similarity and the amount of strangers followed - moderated these relationships. Results from a paper survey among n = 266 British adolescents confirm the hypothesis that those adolescents who compare more strongly on Instagram also report more inspiration from Instagram use. While benign envy positively mediated this relationship, malicious envy worked in the opposite direction, indicating the need to distinguish these two types of envy in future research. In addition, while the amount of strangers followed did not significantly affect the relationships between social comparison, envy, and inspiration, higher perceived network homophily positively moderated the relationship between social comparison and inspiration by eliciting more benign and less malicious envy. Results overall suggest that social comparisons on Instagram may be more inspiring when adolescents compare themselves to similar others and avoid unachievable false role models in their online networks.
CRIS-Team Scopus Importer:2021-02-02
Keywords: envy; homophily; inspiration; Instagram; social comparison; strangers

Instagram inspiration: How upward comparison on social network sites can contribute to well-being - Meier, Adrian; Gilbert, Alicia; Boerner, Sophie; Possler, Daniel (Journal of Communication, 2020)
Passive exposure to others' positive self-presentations on social network sites (SNS) such as Instagram has been repeatedly associated with reduced well-being, particularly by triggering upward social comparison and envy. However, prior research has largely neglected that upward comparisons on SNS may also facilitate positive outcomes, specifically media-induced inspiration, a motivational state highly conducive to well-being. We conducted two experiments that tested whether and how cognitive-affective processing of visual SNS postings results in inspiration. Study 1 (N = 270) provides first evidence that users react to more positive, optimized Instagram nature and travel posts with stronger upward comparison, which facilitates inspiration via an assimilative emotional reaction (benign envy), thus enhancing well-being. The pre-registered Study 2 (N = 408) replicates these findings. Overall, results indicate that users can be inspired from comparing upwards on SNS, which may briefly improve their well-being. We discuss boundary conditions and implications for future communication research.
Keywords: Social network sites; well-being; social comparison; envy; media-induced inspiration

Instagram Inspiration: Investigating content and channel effects on upward social comparison, envy, and inspiration from Instagram use - Meier, Adrian; Gilbert, Alicia; Boerner, Sophie; Possler, Daniel (11th Biannual Conference of the Media Psychology division of the DGPs, 2019)

Instagram inspiration: Upward comparisons can contribute to well-being - Meier, Adrian; Gilbert, Alicia; Boerner, Sophie; Possler, Daniel (70th Annual Conference of the ICA, 2020)

Internet use and procrastination: Results from a German probability sample - Reinecke, Leonard; Meier, Adrian; Aufenanger, Stefan; Beutel, Manfred E.; Dreier, Michael; Quiring, Oliver; Stark, Birgit; Woelfling, Klaus; Müller, Kai W. (9th Biennial Conference of the Media Psychology division of the DGPs, 2015)

Just one more episode: Predictors of procrastination with television and implications for sleep quality - Exelmans, Liese; Meier, Adrian; Reinecke, Leonard; Van Den Bulck, Jan (68th Annual Conference of the ICA, 2018)

Just one more episode: Predictors of procrastination with television and implications for sleep quality - Exelmans, Liese; Meier, Adrian; Reinecke, Leonard; Van Den Bulck, Jan (Mass Communication and Society, 2019)
Sleep experts have raised concern over the effects of electronic media use on sleep. To date, few studies have looked beyond the effects of duration and frequency of media exposure or examined the underlying mechanisms of this association. As procrastinatory media use has been related to lower well-being, we used data from two survey studies (N1 = 821, N2 = 584) to investigate (a) predictors of procrastinatory TV viewing and (b) the link between procrastinatory TV viewing and sleep quality. Findings from both studies indicate that those with a stronger viewing habit, higher TV involvement, and an eveningness preference reported more procrastinatory TV viewing. Procrastinatory TV viewing was related to subjective sleep quality, sleep latency, sleep efficiency, and daytime dysfunction. This association was fully mediated by perceived stress. As sleep is key for the replenishment of self-control, procrastinators may be setting themselves up to fail at self-regulating, a situation exacerbated by the omnipresence of media in today’s society.
CRIS-Team Scopus Importer:2021-02-02

License to procrastinate: Is self-forgiveness for online procrastination driven by self-licensing or self-compassion? - Klingelhoefer, Julius; Meier, Adrian; Meltzer, Christine E.; Reinecke, Leonard (73rd Annual Conference of the International Communication Association, 2023)

Logging media non-use? A computational assessment of digital disconnection with smartphone logging data - Klingelhoefer, Julius; Gilbert, Alicia; Meier, Adrian; Adrian, Christoph; Reinecke, Leonard (13th Conference of the Media Psychology Division of the DGPs, 2023)

Log on, log off, repeat? Motivations and well-being effects of digital disconnection in everyday life - Klingelhoefer, Julius; Gilbert, Alicia; Meier, Adrian (73rd Annual Conference of the International Communication Association, 2023)

Longitudinal links between the positivity bias, inspiration and envy: The role of social media literacy - Schreurs, Lara; Meier, Adrian; Vandenbosch, Laura (72nd Annual Conference of the ICA, 2022)

Mechanisms linking social media use to adolescent mental health vulnerability - Orben, Amy; Meier, Adrian; Dalgleish, Tim; Blakemore, Sarah Jayne (Nature Reviews Psychology, 2024)
Research linking social media use and adolescent mental health has produced mixed and inconsistent findings and little translational evidence, despite pressure to deliver concrete recommendations for families, schools and policymakers. At the same time, it is widely recognized that developmental changes in behaviour, cognition and neurobiology predispose adolescents to developing socio-emotional disorders. In this Review, we argue that such developmental changes would be a fruitful focus for social media research. Specifically, we review mechanisms by which social media could amplify the developmental changes that increase adolescents’ mental health vulnerability. These mechanisms include changes to behaviour, such as sharing risky content and self-presentation, and changes to cognition, such as modifications in self-concept, social comparison, responsiveness to social feedback and experiences of social exclusion. We also consider neurobiological mechanisms that heighten stress sensitivity and modify reward processing. By focusing on mechanisms by which social media might interact with developmental changes to increase mental health risks, our Review equips researchers with a toolkit of key digital affordances that enables theorizing and studying technology effects despite an ever-changing social media landscape.
CRIS-Team Scopus Importer:2024-05-17

Media entertainment as guilty pleasure? The appraisal of media use, self-control, and entertainment (AMUSE) model - Reinecke, Leonard; Meier, Adrian (The Oxford Handbook of Entertainment Theory, 2021)
Using media, specifically those that offer entertainment, frequently conflicts with other goals and obligations in daily life. Users can manage these conflicts either by applying self-control and upholding their goals, or by giving in to media temptations, which elicits negative emotional appraisals such as guilt that potentially spoil entertainment experiences. Currently, a systematic integration of self-control and entertainment theory is direly needed to guide future work in this area. The goals of the present chapter are thus threefold: (1) It provides a theoretical explication of the central components of self-control and subsequently (2) introduces the appraisal of media use, self-control, and entertainment (AMUSE) model. The AMUSE model systematizes the available empirical evidence on the role of self-control for the selection, processing, and effects of (entertaining) media content and, on this basis, the chapter (3) provides testable propositions for future research.<br
Keywords: self-control; appraisal; media entertainment; hedonic; eudaimonic; self-conscious emotions; media selection; message processing; media effects

Methodenworkshop: In-situ-Forschung in der Lehre: Inhaltliche und didaktische Konzepte für die Vermittlung situationsbezogener Forschungsmethoden - Meier, Adrian; Fecke, Malin; Fehr, Ada; Schlütz, Daniela; Karnowski, Veronika; Naab, Teresa K.; Schnauber-Stockmann, Anna (67th Annual Conference of the DGPuK, 2022)

Mindful everyday disconnection — Well-being effects of being mindfully (dis-)connected - Klingelhoefer, Julius; Meier, Adrian (73rd Annual Conference of the International Communication Association, 2023)

Mind the gap: A systematic investigation of temporal dimensions in experience sampling using smartphone log data - Klingelhoefer, Julius; Gilbert, Alicia; Adrian, Christoph; Meier, Adrian (Conference of the Society of Ambulatory Assessment (SAA), 2025)

Mind-wandering and mindfulness as mediators of the relationship between online vigilance and well-being - Johannes, Niklas; Veling, Harm; Dora, Jonas; Meier, Adrian; Reinecke, Leonard; Buijzen, Moniek (Cyberpsychology Behavior and Social Networking, 2018)
As mobile technology allows users to be online anywhere and at all times, a growing number of users report feeling constantly alert and preoccupied with online streams of online information and communication-a phenomenon that has recently been termed online vigilance. Despite its growing prevalence, consequences of this constant orientation toward online streams of information and communication for users' well-being are largely unclear. In the present study, we investigated whether being constantly vigilant is related to cognitive consequences in the form of increased mind-wandering and decreased mindfulness and examined the resulting implications for well-being. To test our assumptions, we estimated a path model based on survey data (N = 371). The model supported the majority of our preregistered hypotheses: online vigilance was indeed related to mind-wandering and mindfulness, but only mindfulness mediated the relationship with decreased well-being. Thus, those mentally preoccupied with online communication were overall less satisfied with their lives and reported less affective well-being when they also experienced reduced mindfulness.
CRIS-Team Scopus Importer:2021-02-02
Keywords: mind-wandering; mindfulness; smartphones; vigilance; well-being

Mobile social media habits and procrastination among adolescents: Investigating between-person, within-person, and person-specific associations - Meier, Adrian; Beyens, Ine; Pouwels, J. Loes; Siebers, Teun; Valkenburg, Patti M. (72nd Annual Conference of the ICA, 2022)

Momentary Motivations for Digital Disconnection: An Experience Sampling Study - Klingelhoefer, Julius; Gilbert, Alicia; Meier, Adrian (74th Annual Conference of the International Communication Association, 2024)

Momentary motivations for digital disconnection: an experience sampling study - Klingelhoefer, Julius; Gilbert, Alicia; Meier, Adrian (Journal of Computer-Mediated Communication, 2024)
A much-discussed solution for undesirable (over-)use of mobile technologies lies in digital disconnection. Reasons for why individuals reduce their digital media use have been assessed mostly cross-sectionally without accounting for various disconnection practices across everyday situations. This study focuses on three motivations to disconnect that can vary between situations: to (a) avoid distractions, (b) improve wellbeing, and (c) be more present. A 14-day experience sampling study with 230 young adults (Mage ¼ 25.31, SD¼ 4.50) yielded 7,360 situations of disconnective behavior. Multilevel regression analyses show that motivations to avoid distractions and to be more present were relevant for disconnection on the situational level. However, a person’s average level of these motivations did not predict disconnective behavior. The wellbeing motivation was not associated with disconnection either between or within participants. Additional analyses explore variations across time and different levels of digital disconnection.
CRIS-Team Scopus Importer:2024-09-06
Keywords: digital disconnection; digital well-being; experience sampling; motivation; non-use

More interruptions and fewer accomplishments? How smartphone habits increase the frequency of procrastination and decrease hedonic and eudaimonic well-being in everyday life - Meier, Adrian; Reinecke, Leonard (10th Biennial Procrastination Research Conference, 2017)

Navigation Trajectories in Smartphone App Use: Towards a Digital Disconnection Perspective - Yang, Ellie; Klingelhoefer, Julius; Gilbert, Alicia; Dai, Xiaotian; Meier, Adrian (75th Annual Conference of the International Communication Association, 2025)

Neither pleasurable nor virtuous: Procrastination links smartphone habits and messenger checking behavior to decreased hedonic as well as eudaimonic well-being - Meier, Adrian (67th Annual Conference of the ICA, 2017)

New media, new effects? Introducing the Technology Equivalence Approach (TEA) - Meier, Adrian (12th Biannual Conference of the Media Psychology division of the DGPs, 2021)

Of sweet temptations and bitter aftertaste: Self-control as a moderator of the effects of media use on well-being - Hofmann, Wilhelm; Reinecke, Leonard; Meier, Adrian (The Routledge Handbook of Media Use and Well-Being: International Perspectives on Theory and Research on Positive Media Effects, 2017)
CRIS-Team Scopus Importer:2021-02-02

Online communication and mental health: Insights and implications from three systematic literature reviews - Meier, Adrian; Domahidi, Emese; Günther, Elisabeth; Reinecke, Leonhard (65th Annual Conference of the DGPuK, 2020)

On the interplay between media entertainment and self-control: The Appraisal of Media Use, Self-Control, and Entertainment (AMUSE) Model - Reinecke, Leonhard; Meier, Adrian (65th Annual Conference of the DGPuK, 2020)

Permanently on and never switching off? The role of online vigilance as a source of digital stress - Reinecke, Leonard; Meier, Adrian; Klimmt, Christoph; Hefner, Dorothée; Vorderer, Peter (10th Biennial Conference of the Media Psychology division of the DGPs, 2017)

Permanently online—always stressed out? The effects of permanent connectedness on stress experiences - Freytag, Anna; Knop-Huelss, Katharina; Meier, Adrian; Reinecke, Leonard; Hefner, Dorothée; Klimmt, Christoph; Vorderer, Peter (Human Communication Research, 2021)
Concerns have been expressed that permanent online connectedness might negatively affect media user’s stress levels. Most research has focused on negative effects of specific media usage patterns, such as media multitasking or communication load. In contrast, users’ cognitive orientation toward online content and communication has rarely been investigated. Against this backdrop, we examined whether this cognitive orientation (i.e., online vigilance with its three dimensions salience, reactibility, monitoring) is related to perceived stress at different timescales (person, day, and situation level), while accounting for the effects of multitasking and communication load. Results across three studies showed that, in addition to multitasking (but not communication load), especially the cognitive salience of online communication is positively related to stress. Our findings are discussed regarding mental health implications and the origins of stress.<br

Permanently online and always stressed out? The effects of online vigilance on digital stress experiences - Freytag, Anna; Knop-Huelss, Katharina; Hefner, Dorothée; Klimmt, Christoph; Reinecke, Leonard; Meier, Adrian; Vorderer, Peter (69th Annual Conference of the ICA, 2019)

Permanently online and permanently connected: Development and validation of the online vigilance scale - Reinecke, Leonard; Klimmt, Christoph; Meier, Adrian; Reich, Sabine; Hefner, Dorothée; Knop-Huelss, Katharina; Rieger, Diana; Vorderer, Peter (67th Annual Conference of the ICA, 2017)

Permanently online and permanently connected: Development and validation of the online vigilance scale - Reinecke, Leonard; Klimmt, Christoph; Meier, Adrian; Reich, Sabine; Hefner, Dorothee; Knop-Huelss, Katharina; Rieger, Diana; Vorderer, Peter (PLoS ONE, 2018)
Smartphones and other mobile devices have fundamentally changed patterns of Internet use in everyday life by making online access constantly available. The present paper offers a theoretical explication and empirical assessment of the concept of online vigilance, referring to users’ permanent cognitive orientation towards online content and communication as well as their disposition to exploit these options constantly. Based on four studies, a validated and reliable self-report measure of online vigilance was developed. In combination, the results suggest that the Online Vigilance Scale (OVS) shows a stable factor structure in various contexts and user populations and provides future work in communication, psychology, and other social sciences with a new measure of the individual cognitive orientation towards ubiquitous online communication.
CRIS-Team Scopus Importer:2021-02-02

Permanently online and permanently procrastinating? The mediating role of Internet use for the effects of trait procrastination on psychological health and well-being - Reinecke, Leonard; Meier, Adrian; Aufenanger, Stefan; Beutel, Manfred E.; Dreier, Michael; Quiring, Oliver; Stark, Birgit; Woelfling, Klaus; Mueller, Kai W. (New Media & Society, 2018)
A growing number of studies suggest that Internet users frequently utilize online media as “tools for procrastination.” This study thus investigated the relationship between trait procrastination, Internet use, and psychological well-being in a representative sample of N = 1,577 German Internet users. The results revealed that trait procrastination was associated with an increased use of leisure-related online content and impaired control over Internet use. As a result, Internet users high in trait procrastination showed a higher risk of experiencing negative consequence of Internet use in other life domains. These negative repercussions of insufficiently self-regulated Internet use partially accounted for the correlation between trait procrastination and impaired well-being (i.e. stress, anxiety, and depression). These findings underline the role of online media as an instrument for dysfunctional task delay among Internet users. Implications of the results are discussed with regard to media use and self-control in general and procrastinatory media use in specific.
CRIS-Team Scopus Importer:2021-02-02
Keywords: Habit; Internet use; procrastination; self-control; well-being

Permanently online and permanently procrastinating? The mediating role of Internet use for the effects of trait procrastination on psychological well-being - Reinecke, Leonard; Meier, Adrian; Aufenanger, Stefan; Beutel, Manfred E.; Dreier, Michael; Quiring, Oliver; Stark, Birgit; Woelfling, Klaus; Müller, Kai W. (66th Annual Conference of the ICA, Fukuoka, 2016)

Positive conditioning via newspaper headlines reduces negative implicit stereotypes against muslims - Meier, Adrian; Schemer, Christian; Viererbl, Benno; Busche, Nora; Schmidt, Sophia (61st Annual Conference of the DGPuK, 2016)

Positive effects from upward social comparison on social network sites? How Instagram usage can elicit inspiration and increase well-being - Meier, Adrian; Gilbert, Alicia; Börner, Sophie; Possler, Daniel (25th Annual Conference of the Media Uses and Effects division of the DGPuK, 2019)

Possible Futures All at Once: Time Frame and Time Lag in Short-Term Longitudinal Media Effects Research on Well-Being - Klingelhoefer, Julius; Gilbert, Alicia; Adrian, Christoph; Meier, Adrian (75th Annual Conference of the International Communication Association, 2025)

Possible futures all at once: time frame and time lag in short-term longitudinal media effects research on well-being - Klingelhoefer, Julius; Gilbert, Alicia; Adrian, Christoph; Meier, Adrian (Journal of Communication, 2025)
When assessing media effects, we seldom consider how they change over time. Especially with the prevalence of smartphone use as short-lived, fragmented media use, a systematic approach to temporal dimensions is crucial, particularly to understand mixed effects of smartphone use on situational well-being. We employ a multiverse approach to assess the influence of two central temporal dimensions in intensive longitudinal media effects research: Time frame and time lag. We combine mobile experience sampling (T1 = 2,859, T2 = 7,708) and log data (K1 = 71,807, K2 = 259,004) from N1 = 84 and N2 = 192 participants. Building on theorizing on time in media effects research, we propose four patterns of how short-term effects on situational well-being unfold: they may follow processes of ephemerality (fleeting effects), inertia (delayed onset), reversal (changing directions), or there are no changes over time. We discuss theoretical implications and give recommendations for future studie

Procrastination out of habit? The role of impulsive versus reflective media selection in procrastinatory media use - Schnauber-Stockmann, Anna; Meier, Adrian; Reinecke, Leonard (Media Psychology, 2018)
The pervasive access to media options seriously challenges users’ self-regulatory abilities. One example of deficient self-regulation in the context of media use is procrastination—impulsively ‘giving in’ to available media options despite goal conflicts with more important tasks. This study investigaes procrastinatory media use across 3 types of media (TV, computer, smartphone) from a dual-systems perspective, taking both person-level and situation-level predictors into account. Results from a 14-day long diary study (N = 347) suggest that procrastinatory media use is driven by automatic media selection, which is facilitated by strong media habits (person level) and low motivation for behavioral control (situation level). The results underline the value of a dual-systems perspective on media choices in our media-saturated environment.
CRIS-Team Scopus Importer:2021-02-02

Procrastination out of habit? The role of impulsive vs. reflective media selection in procrastinatory media use - Schnauber-Stockmann, Anna; Meier, Adrian; Reinecke, Leonard (67th Annual Conference of the ICA, 2017)

Reflective vs. impulsive media selection as a key predictor of procrastinatory media use - Schnauber-Stockmann, Anna; Meier, Adrian; Reinecke, Leonard (23rd Annual Conference of the Media Uses and Effects division of the DGPuK, 2017)

Seeking Serendipity Online: Eine explorative Studie zum Suchen und Finden von Inspiration in sozialen Medien - Ernst, Alicia; Gilbert, Alicia; Meier, Adrian (29th Annual Conference of the Media Uses and Effects division of the DGPuK, 2023)

Self-control failure or coping strategy? Facebook-induced strains as a consequence of procrastination and escapism - Meier, Adrian; Meltzer, Christine E.; Reinecke, Leonhard (22nd Annual Conference of the Media Uses and Effects division of the DGPu, 2016)

Sharing awe: Vicarious transcendent experiences via social media - Possler, Daniel; Meier, Adrian; Boerner, Sophie; Gilbert, Alicia; Scherer, Helmut (12th Biannual Conference of the Media Psychology division of the DGPs, 2021)

Social comparison and envy on social media: A critical review - Meier, Adrian; Johnson, Benjamin K. (72nd Annual Conference of the ICA, 2022)

Social comparison and envy on social media: A critical review - Meier, Adrian; Johnson, Benjamin K. (Current Opinion in Psychology, 2022)
There is both public and scholarly concern that (passive) social media use decreases well-being by providing a fertile ground for harmful (upward) social comparison and envy. The present review critically summarizes evidence on this assumption. We first comprehensively synthesize existing evidence, including both prior reviews and the most recent publications (2019–2021). Results show that earlier research finds social comparison and envy to be common on social media and linked to lower well-being. Yet, increasingly, newer studies contradict this conclusion, finding positive links to well-being as well as heterogeneous, person-specific, conditional, and reverse or reciprocal effects. The review identifies four critical conceptual and methodological limitations of existing evidence, which offer new impulses for future research.<br
Keywords: social comparison; envy; well-being; social media; passive use; critical review

Social comparison on social media and mental health: A scoping review - Arenz, Anisha; Meier, Adrian; Reinecke, Leonard (Beiträge zur Jahrestagung der Fachgruppe Rezeptions- und Wirkungsforschung 2022, 2023)
Social media offer their users a variety of opportunities for online self-presentation and thus represent an optimal environment for social comparisons. With the increasing popularity of social media, there is growing concern in public and scientific discourse about negative effects of online social comparisons on users’ mental health. Research output on this topic is increasing rapidly, making the field more heterogeneous and difficult to oversee. This scoping review therefore aims to provide a systematic mapping of the fragmented research field on social media comparisons and mental health. Using predefined inclusion criteria, 131 quantitative studies were systematically identified to map the research field. The results showed that the number of studies has grown since 2011 and that first authors from the United States and Psychology departments were the main contributors. With regard to the comparison directions, comparison dimensions, and indicators of mental health examined, the analyses demonstrate that the studies primarily focused on upward comparisons on diverse dimensions and hedonic well-being, whereas downward comparisons and other facets of mental health are currently under-represented in the fiel

Social media and mental health: Reviewing effects on eudaimonic well-being - Meier, Adrian; Reinecke, Leonard (71st Annual Conference of the ICA, 2021)

Social media and mental health: Reviewing effects on eudaimonic well-being - Meier, Adrian; Reinecke, Leonard (Emotions in the digital world: Exploring affective experience and expression in online interactions, 2023)

Social media and well-being at work, at home, and in-between: a review - Klingelhoefer, Julius; Meier, Adrian (Research handbook on digital sociology, 2023)
With increasing relevance of collaborative technologies in the workplace and flexible work arrangements, concerns and hopes about associations between social media use and well-being arise. Social media can introduce content and demands from the work context into the home and vice-versa. This narrative review of k = 39 publications addresses work-inconsistent and home-inconsistent social media use, particularly during remote work. The reviewed studies show that social media use can be associated with negative outcomes such as stress. At the same time, many studies found associations with beneficial outcomes such as higher job satisfaction. These conclusions are limited by the predominantly cross-sectional survey designs and inconsistent conceptualization and measurement of social media use. We suggest improvements and call for more longitudinal and experimental studies to advance the understanding of social media use and well-being at the work-home interface.<br
Keywords: social media; ICTs; well-being; work-home interface; remote work; narrative review

Social media use and its impact on adolescent mental health: An umbrella review of the evidence - Valkenburg, Patti M.; Meier, Adrian; Beyens, Ine (Current Opinion in Psychology, 2022)
Literature reviews on how social media use affects adolescent mental health have accumulated at an unprecedented rate of late. Yet, a higher-level integration of the evidence is still lacking. We fill this gap with an up-to-date umbrella review, a review of reviews published between 2019 and mid-2021. Our search yielded 25 reviews: seven meta-analyses, nine systematic, and nine narrative reviews. Results showed that most reviews interpreted the associations between social media use and mental health as 'weak' or 'inconsistent,' whereas a few qualified the same associations as 'substantial' and 'deleterious.' We summarize the gaps identified in the reviews, provide an explanation for their diverging interpretations, and suggest several avenues for future research.
CRIS-Team WoS Importer:2021-10-29

Special issue: Social media and well-being - Valkenburg, Patti M.; Beyens, Ine; Meier, Adrian; Vanden Abeele, Mariek (Current Opinion in Psychology, 2022)
The effect of social media use on well-being is among the hottest debates around the world. This special issue brings together scholars from the social and behavioral sciences to reflect on the breadth of research published in recent years. The collaborative contributions of these scholars resulted in 26 articles on the effects of social media use on well-being. Beyond synthesizing the state of the literature, the invited articles address key risk and resilience factors, such as self-esteem, cyberbullying, body image, and (romantic) relationships. Additionally, they discuss important mechanisms to explain the effects of social media use on well-being, such as social comparison, self-regulation, and social displacement. Finally, they dedicate special attention to the uses and effects of social media among specific groups (older people, parents), contexts (the workplace) and regions (the Global South

Stopping media entertainment viewing: Self-control and disengagement processes on Netflix - Gilbert, Alicia; Reinecke, Leonard; Meier, Adrian; Baumgartner, Susanne; Kühne, Rinaldo (72nd Annual Conference of the ICA, 2022)

Studying problems, not problematic usage: Do mobile checking habits increase procrastination and decrease well-being? - Meier, Adrian (Mobile Media and Communication, 2022)
Most prior research on the effects of mobile and social media on well-being has worked from either the “technology addiction” or “screen time” approach. Yet these frameworks struggle with considerable conceptual and methodological limitations. The present study discusses and tests an established but understudied alternative, the technology habit approach. Instead of conflating mobile usage with problems (i.e., addictive/problematic usage) or ignoring users’ psychological engagement with mobiles (i.e., screen time), this approach investigates how person-level (habit strength) and day-level aspects of mobile habits (perceived interruptions and the urge to check) contribute to a key problem outcome, procrastination, as well as affective well-being and meaningfulness. In a five-day diary study with N = 532 student smartphone users providing N = 2,331 diary entries, mobile checking habit strength, perceived interruptions, and the urge to check together explained small to moderate amounts of procrastination. Procrastination, in turn, was linked to lower affective well-being and meaningfulness. Yet mobile habits showed only very small or no direct associations with affective well-being and meaningfulness. By separating habitual mobile connectivity from problem outcomes and well-being measures, this research demonstrates a promising alternative to the study of digital well-being.
CRIS-Team Scopus Importer:2021-08-20
Keywords: addiction; mental health; mobile connectivity; procrastination; screen time; technology habits; well-being

Taking a break offline: Situational associations of digital disconnection and well-being - Gilbert, Alicia; Klingelhoefer, Julius; Meier, Adrian (Conference of the Society of Ambulatory Assessment (SAA), 2025)

The appraisal of media use, self-control, and entertainment (AMUSE) model - Meier, Adrian; Reinecke, Leonhard (70th Annual Conference of the ICA, 2020)

The big picture: Mapping a decade of research on social media use and well-being - Hancock, Jeff; Liu, Sunny Xun; French, Megan; Meier, Adrian; Domahidi, Emese; Günther, Elisabeth; Reinecke, Leonard; Bayer, Joseph; Marker, Caroline; Gnambs, Timo; Appel, Markus; Toma, Catalina; et al. (68th Annual Conference of the ICA, 2018)

The (not so) guilty mouse potato: How appraisal of online procrastination changes the recovery outcome after online media use - Meier, Adrian; Reinecke, Leonard; Meltzer, Christine E. (65th Annual Conference of the ICA, 2015)

The positive side of social comparison on SNS: Investigating inspiration on Instagram - Meier, Adrian; Schäfer, Svenja (68th Annual Conference of the ICA, 2018)

The positive side of social comparison on social network sites: How envy can drive inspiration on Instagram - Meier, Adrian; Schaefer, Svenja (Cyberpsychology Behavior and Social Networking, 2018)
A growing body of research finds social network sites (SNS) such as Instagram to facilitate social comparison and the emotional experience of envy in everyday life, with harmful effects for users' well-being. Yet, previous research has exclusively focused on the negative side of social comparison and envy on SNS. Thereby, it has neglected two important aspects: (a) comparison processes can also elicit a beneficial emotional reaction to other users' online self-presentations (i.e., benign envy) and, thus, (b) comparisons can be motivating, with positive outcomes for well-being. The present study aims at closing this research gap by investigating how social comparisons and envy on SNS are related to inspiration, a complex motivational state. Due to its specific characteristics of a creative and aesthetic visual culture, we focus our investigation on Instagram. A structural equation modeling mediation analysis with data from N = 385 Instagram users reveals that the intensity of social comparisons on Instagram was positively related to inspiration and that this relationship was fully mediated by benign envy. Furthermore, inspiration on Instagram was related to increased positive affect. Results of this study underline that to understand the effects of SNS on well-being, we also need to consider the positive motivational side of social comparison and envy.
CRIS-Team Scopus Importer:2021-02-02
Keywords: Instagram; social comparison; envy; inspiration; well-being

The positive side of social comparisons on SNS: How envy can drive inspiration on Instagram - Meier, Adrian; Schäfer, Svenja; Melching, Vanessa; Bonni, Kerstin (10th Biennial Conference of the Media Psychology division of the DGPs, 2017)

The relationship between computer-mediated communication and mental health—A meta-review of systematic reviews and meta-analyses - Meier, Adrian; Reinecke, Leonhard (68th Annual Conference of the ICA, 2018)

The relationship between online vigilance and affective well-being in everyday life: Combining smartphone logging with experience sampling - Johannes, Niklas; Meier, Adrian; Reinecke, Leonard; Ehlert, Saara; Setiawan, Dinda Nuranissa; Walasek, Nicole; Dienlin, Tobias; Buijzen, Moniek; Veling, Harm (Media Psychology, 2021)
Through communication technology, users find themselves constantly connected to others to such an extent that they routinely develop a mind-set of connectedness. This mind-set has been defined as online vigilance. Although there is a large body of research on media use and well-being, the question of how online vigilance impacts well-being remains unanswered. In this preregistered study, we combine experience sampling and smartphone logging to address the relation of online vigilance and affective well-being in everyday life. Seventy-five Android users answered eight daily surveys over five days (N = 1,615) whilst having their smartphone use logged. Thinking about smartphone-mediated social interactions (i.e., the salience dimension of online vigilance) was negatively related to affective well-being. However, it was far more important whether those thoughts were positive or negative. No other dimension of online vigilance was robustly related to affective well-being. Taken together, our results suggest that online vigilance does not pose a serious threat to affective well-being in everyday life.
CRIS-Team Scopus Importer:2021-02-02

The relationship between procrastinatory television viewing and sleep quality: Drivers and underlying mechanisms - Exelmans, Liese; Meier, Adrian; Reinecke, Leonard; Van Den Bulck, Jan (Etmaal van de Communicatiewetenschap, 2018)

The relationship between trait procrastination, internet use, and psychological functioning: Results from a community sample of German adolescents - Reinecke, Leonard; Meier, Adrian; Beutel, Manfred E.; Schemer, Christian; Stark, Birgit; Woelfling, Klaus; Mueller, Kai W. (Frontiers in Psychology, 2018)
Adolescents with a strong tendency for irrational task delay (i.e., high trait procrastination) may be particularly prone to use Internet applications simultaneously to other tasks (e.g., during homework) and in an insufficiently controlled fashion. Both Internet multitasking and insufficiently controlled Internet usage may thus amplify the negative mental health implications that have frequently been associated with trait procrastination. The present study explored this role of Internet multitasking and insufficiently controlled Internet use for the relationship between trait procrastination and impaired psychological functioning in a community sample of N = 818 early and middle adolescents. Results from multiple regression analyses indicate that trait procrastination was positively related to Internet multitasking and insufficiently controlled Internet use. Insufficiently controlled Internet use, but not Internet multitasking, was found to partially statistically mediate the association between trait procrastination and adolescents' psychological functioning (i.e., stress, sleep quality, and relationship satisfaction with parents). The study underlines that adolescents with high levels of trait procrastination may have an increased risk for negative outcomes of insufficiently controlled Internet use.
CRIS-Team Scopus Importer:2021-02-02
Keywords: Adolescents; Internet use; Mental health; Procrastination; Self-control

“Tomorrow: @House of Cards” – (Unintended) effects of pop culture references on the perception of politicians - Meier, Adrian; Peter, Christina (22nd Annual Conference of the Media Uses and Effects division of the DGPuK, 2016)

Too amused to stop? Selbstkontrolle und Unterhaltungserleben bei der Netflix-Nutzung - Gilbert, Alicia; Reinecke, Leonard; Meier, Adrian; Baumgartner, Susanne; Kühne, Rinaldo; Dietrich, Felix (29th Annual Conference of the Media Uses and Effects division of the DGPuK, 2023)

Too amused to stop? Self-control and the disengagement process on Netflix - Gilbert, Alicia; Reinecke, Leonard; Meier, Adrian; Baumgartner, Susanne E.; Dietrich, Felix (Journal of Communication, 2024)
Consuming media entertainment often challenges recipients' self-control. While past research related self-control almost exclusively to whether individuals engage in media use, it might be equally relevant for the disengagement from media use. Testing core assumptions of the Appraisal of Media Use, Self-Control, and Entertainment (AMUSE) model, the present study investigates the situational interplay of self-control and affective appraisals in predicting disengagement from Netflix use. Preregistered hypotheses were tested based on an event-contingent experience sampling design, in which 205 adult Netflix users in the Netherlands and Germany were tracked and surveyed for two weeks. Results demonstrate that disengagement is contingent upon enjoyment and appreciation and that enjoyment, in turn, can be "spoiled"by feeling guilty. Self-control influenced goal conflict and enjoyment throughout the reception process. We discuss opportunities for modeling disengagement from media use with situational research approaches.
CRIS-Team Scopus Importer:2024-11-08
Keywords: disengagement; experience sampling; media entertainment; Netflix; self-control

Too much or too little messaging? Situational determinants of guilt about mobile messaging - Halfmann, Annabell; Meier, Adrian; Reinecke, Leonard (Journal of Computer-Mediated Communication, 2021)
Mobile messaging has been associated with guilt. Guilt about too much messaging may result from self-control failures during goal conflicts. Conversely, guilt about too little messaging may result from violating the salient norm to be available. This research considers both boundary conditions of guilt about mobile communication—goal conflicts and availability norm salience—simultaneously for the first time. We conducted two preregistered experiments to investigate their interplay. Results from a vignette experiment, but not from a laboratory experiment, support the hypotheses that goal conflicts trigger guilt about using messengers and that guilt about not using messengers arises if the availability norm is salient. In both studies, using messengers elicited more guilt than not using messengers. The boundary conditions did not interact in influencing guilt. Overall, this research emphasizes the importance of self-control, norms, and usage contexts when studying effects of mobile media use on emotional well-being.<br

Too much or too little messaging? Situational determinants of guilt about mobile messenger usage - Halfmann, Annabell; Meier, Adrian; Reinecke, Leonhard (70th Annual Conference of the ICA, 2020)

Trapped between goal conflict and availability norm? How users' mobile messaging behavior during task engagement influences negative self-conscious emotions - Halfmann, Annabell; Meier, Adrian; Reinecke, Leonard (Journal of Media Psychology, 2024)
An increasing number of studies indicate that individuals have difficulties in exerting self-control over media use, such as mobile messaging. Specifically, individuals frequently experience that their messenger use conflicts with primary goals (e.g., work tasks), which may cause negative self-conscious emotions such as guilt. At the same time, not checking and answering messages violates a now widely established availability norm, which may trigger negative self-conscious emotions as well. The current study, therefore, tests how goal conflicts and connection cues interact in influencing users' negative self-conscious emotions about their messenger usage behavior. Drawing on self-control research in conjunction with self-determination theory and theoretical approaches to social norms, we derived hypotheses on the boundary conditions under which the frequency of messenger use causes negative self-conscious emotions. We thereby significantly extend previous research on the self-regulation of mobile media use, which largely assumes that self-control failure results from users' intrinsic motivation to experience need satisfaction and pleasure and tends to overlook the fact that mediated communication is often extrinsically motivated due to the availability norm. The hypotheses were tested based on a preregistered laboratory experiment.
CRIS-Team Scopus Importer:2023-05-19
Keywords: availability; messenger use; self-conscious emotions; self-control; task engagement

Trapped between self-control failure and norm violation: How user's mobile messaging behavior during task engagement influences feelings of guilt - Halfmann, Annabell; Meier, Adrian; Reinecke, Leonard (11th Biannual Conference of the Media Psychology division of the DGPs, 2019)

(Unintended) effects of pop culture references on the perception of politicians - Peter, Christina; Meier, Adrian; Koch, Thomas (66th Annual Conference of the ICA, 2016)

Unravelling Passive Social Media Use Through Screenomes - Yee, Andrew Z. H.; Krause, Hannes-Vincent; Meier, Adrian; Ng, Li Yin; Loy, Guan Peng (74th Annual ICA Conference, 2024)
The active-passive framework to social media use and well-being promised nuanced insights, yet effects of passive use have been mixed. One reason could be the enormous heterogeneity of the ‘passive use’ concept, which encompasses various social media features, actions, and contents. This study applies the conceptual lenses of the hierarchical CMC taxonomy and social media content genres to unpack and explore this heterogeneity of passive social media use. We use a random sample of smartphone screenshots (‘screenomics’) drawn from 703,827 sequential screenshots collected from 20 participants over a two-week period to content analyze 10,000 screenshots. Results reveal substantial heterogeneity and patterns within passive use across four analytical levels: branded application, feature, modality, and content topics/genres. As the effects of social media on well-being may often be caused by content or design features, our study provides insights into how passive use can be broken down into more meaningful units of analysi
Keywords: social media; active-passive model; screenomics; well-being; content analysis

Voicing concerns: Alternative perspectives on problematic mobile media use beyond the disease model - Vanden Abeele, Mariek; Meier, Adrian; Bayer, Joseph; Johannes, Niklas; Lee, Edmund Wei Jian (15th Annual Mobile Pre-Conference of the ICA, 2018)

“When inspiration doesn’t come to me, I go halfway to meet it” – A theoretical model of how users find inspiration on Instagram - Ernst, Alicia; Meier, Adrian (26th Annual Conference of the Media Uses and Effects division of the DGPuK, 2020)